Disaster Management: Selections of Evacuation Routes Due to Flood Disaster. (2017) - Atmojo, Pranoto Samto; Sachro, Sri Sangkawati
Abstract: A flood is a natural phenomenon that is difficult to avoid. Yet, it becomes problems in an urban area. Due to increase in population and high cost of land in urban areas, people have built their residential places in the areas at risk of inundation. In order to avoid great losses and fatality affected by flooding, a flood disaster management is needed. A study of non physical mitigation, i.e. to establish some alternatives of evacuation routes to some temporary shelters for the casualties was conducted. This research analyzed and selected several evacuation routes that were effective and safe from flooding-based Geographic Information System (GIS). The research was started by analyzing the flood magnitude, inundation area, population density, settlement concentration, temporary shelter locations, topographic condition and existing road system. For this research, the Western Semarang District in Central Java was chosen as a case study area. The results can be used as a model of evacuation approach at the research location, for other flood areas and also for a dam failure.